The forces behind social unrest: Evidence from the Covid-19 pandemic. - Mario Lackner; Uwe Sunde; Rudolf Winter-Ebmer (PLoS ONE)
The unprecedented consequences of the Covid-19 pandemic have raised concerns about the erosion of social cohesion and intensified social unrest, but evidence for such a link and the underlying channels is still lacking. We use a unique combination of nationally representative survey data, event data on social unrest, and data on Covid-19 fatalities and unemployment at a weekly resolution to investigate the forces behind social cohesion and unrest in the context of the strains on public health and the economy due to the pandemic in the USA. The results show that pandemic-related unemployment and Covid-19 fatalities intensified negative emotional stress and led to a deterioration of economic confidence among individuals. The prevalence of negative emotional stress, particularly in economically strained and politically polarized environments, was, in turn, associated with intensified social unrest as measured by political protests. No such link is found for economic perceptions.